CODE SWITCHING IN PAKISTANI ENGLISH (Al-Aasar, 2025)
Code-switching as the speaker's use of multiple language varieties or styles within a single discourse or utterance, or across different interlocutors and communicative contexts.It draws attention to how Pakistan's communication dynamics have been affected by code-switching. In this paper, a mixed method of research is used to switch the code of Pakistani English. This study highlights the various typology of code-switching identified by Poplack namely  inter-sentential switching, and intra-sentential switchingoffering a deeper analysis to enhance the reader’s understanding of English as spoken in Pakistan. It also examines the functions of code-switching in Pakistani English,such as expressing prestige and authority, enhancing clarity and emphasis, signalling modernization and globalization, engaging the audience, and introducing humour or informality which is given by Gumperz (1982).These functions not only ease communication but also reflect the cultural, social, and linguistic dynamics of Pakistani society.